Career training with mentoring programs in higher education: Facilitating career development and employability of graduates. Issue 3 (24th March 2020) - Okolie, Ugochukwu Chinonso; Nwajiuba, Chinyere Augusta; Binuomote, Michael Olayinka; Ehiobuche, Christian; Igu, Ntasiobi Chikezie Nwankwo; Ajoke, Ogungboyega Suliyat
Abstract : Purpose: This study explores how career training with mentoring (CTM) programs work in Nigerian higher education (HE) institutions to foster students' career development and employability of graduates. It also explores how Nigerian HE curriculum can be adequately used to facilitate CTM as well as possible constraints to effective implementation of CTM programs in Nigerian HE institutions. Design/methodology/approach: The study draws on interviews with well-qualified and experienced experts from six Nigerian public universities (each from the 6 geo-political zones of Nigeria), and 20 industries also within the same 6 geo-political zones of Nigeria that were selected for this study using a purposeful sampling technique. The study interviewed 33 experts comprising 21 senior academics at Nigerian universities and 12 industry executives to reveal substantial information about CTM programs in Nigerian HE institutions. Findings: Drawing on the three key themes that emerged during the thematic analysis and linked to social cognitive career theory, it is clear that participants are convinced that CTM can enhance clarity about students' career ambitions, career interests, personal development plans and employability. Findings show that there are some career-related programs or activities that Nigerian HE students are presented with, but the programs have not been effective as to offer graduates quality career guidance and employability skills that employers demand. Acknowledging these, participants recommend establishing CTM centres in all Nigerian HE institutions to provide students with the opportunity to receive quality career advice, coaching and mentoring services while schooling. Practical implications: The findings of this study shed light on varying resources required to cope with the demands of labour market in terms of supply of competent workforce that can contribute to Nigeria's economic growth and development. The findings are highly relevant for Nigeria and other developing countries' policy and research initiatives that aim to promote social inclusion and equity and improve better working conditions for all. The findings also have implications for career development and employability of HE graduates in developing world context. Originality/value: Understanding the role that CTM programs can play in facilitating career development and graduate employability can arguably be of importance within the developing world context. This study, therefore, provides significant suggestions on how to build sustained HEIs and labour market partnership to foster career development and employability of HE graduates through establishing CTM centres in every Nigerian HE institutions.